Evaluation of a Coupled Organic Rankine Cycle Mild Hybrid Architecture for Long-Haul Heavy-Duty Truck ⁎. Issue 5 (2019) - Galuppo, Francesco; Nadri, Madiha; Dufour, Pascal; Reiche, Thomas; Lemort, Vincent
Abstract: Increasing fuel prizes, future CO2 emission legislation as well as new powertrain architectures are the main factors for truck manufacturers to invest into fuel saving technologies. Especially for long haul heavy duty transport and high mean engine loads, Rankine cycle waste heat recovery can lead to significant fuel savings. In this study transient road cycle simulations are performed to compare different Rankine architectures, coupled to a mild hybrid driveline, using tailpipe heat as heat source and ethanol as working fluid. The results show better performance for the indirect cooling strategy. Furthermore the multi-model proportional integral controller is considered as the best controller to fulfill the requirements about safety and performance.